THE EFFECT OF CUSTOMER EXPERIENCE AND SERVICE QUALITY ON TELKOMSEL CUSTOMER LOYALTY - Didi Tarmidi; Aris Frianto Pani (SEAN Institute, 2023)
Telkomsel is one of the country's operators facing customer retention issues in Indonesia. The aim of this study is to determine the influence of customer experience and service quality on Telkomsel's customer loyalty. The research method used in this study is a quantitative method with a descriptive research character. Sampling was performed using a non-probabilistic sampling technique used for targeted sampling of a total of 100 respondents using Telkomsel service provider users in of Bandung city. In turn, the data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results showed that customer experience and service quality had a positive and significant impact on customer loyalty, with a large impact of 39.3% and the remaining 60.7% being influenced by other unstudied factors.